Multiphoton reactive surfaces using ruthenium(II) photocleavable cages - San Miguel, Verónica (2012)
Photoreactive surfaces derived from a new photocleavable surface modification agent and with photosensitivity in the Vis and IR region are described. A ruthenium(II) caged aminosilane, [Ru(bpy) 2(PMe 3)(APTS)](PF 6) 2, was synthesized and attached to silica surfaces. Light irradiation removed the cage and generated surface patterns with reactive amine groups. The photosensitivity of this compound under single (460 nm) and two-photon (900) excitation is demonstrated. Functional patterns with site-selective attachment of other molecular species are described.